Finance without financiers - Epstein, Gerald; Plihon, Dominique; Giannola, Adriano; Weller, Christian (Papeles de Europa, 2009)
In response to the financial crisis of 2007 – 2009, governments in the United States, Europe and elsewhere have invested billions of dollars in financial institutions to prevent them from going bankrupt and from further disrupting the global economy. Despite these massive public bail-outs, a government and "elite" consensus has emerged that these nationalized or quasi-nationalized financial institutions should be privatized as soon as possible, and that, apart from modest changes in financial regulation, our economies should return to the status quo ante financial structure as soon as possible. In short, despite a massively disruptive economic crisis caused by financiers, our best option as a society is to return to a financial system run by these financiers. We disagree. As the crisis reveals, financier dominated finance has a number of crucial flaws: it creates major externalities that contribute to financial and real economic instability; it promotes short-term investment strategies; it contributes to inequality; and it undermines economic efficiency and the achievement of social goals in the real economy. We argue that a better strategy for achieving economic recovery, restructuring and widely shared, sustainable prosperity is to use public investments in the financial sector to build on the successful Post-World War II experiences of publicly oriented financial institutions in Europe and the US to create a stronger presence of "finance without financiers". We provide case studies of the positive and negative experiences with publicly owned and controlled financial institutions in the United States, France, Germany and Italy, and draw lessons for successfully creating more publicly oriented financial institutions moving forward. We emphasize local differences, policy space and "social management" of these financial institutions to ensure that publicly owned financial institutions is, at the same time, genuinely publicly oriented institutions that fit local conditions.